ZNACZENIE KONSTYTUCJI TURECKIEJ Z 1961 ROKU DLA ROZWOJU IDEI PAŃSTWA PRAWNEGO W TURCJI - Adamczyk, Andrzej (Zeszyty Prawnicze, 2016)
THE IMPORTANCE OF THE 1961 TURKISH CONSTITUTION FOR DEVELOPMENT OF THE STATE RULED BY LAW IDEA IN TURKEY Summary The article is devoted to description of the 1961 Turkish Constitution as an important step to bring the idea of the state ruled by law in Turkey. The main lines of the first constitution in republican Turkey, that of 1924, and some political abuses which the Menderes government made in the 1950-1960 period were presented at the beginning of the article for better understanding of novelties brought by the second republican Turkish Constitution of 1961. As regards the main subject of the article, the circumstances of constitutional debates, the constitutional principles, new regulations of the state-individual relations as well as the structure of public authorities in the constitution in question were analyzed.